Cooperative interaction among BMAL1, HSF1, and p53 protects mammalian cells from UV stress. (December 2018) - Kawamura, Genki; Hattori, Mitsuru; Takamatsu, Ken; Tsukada, Teruyo; Ninomiya, Yasuharu; Benjamin, Ivor; Sassone-Corsi, Paolo; Ozawa, Takeaki; Tamaru, Teruya
Abstract The circadian clock allows physiological systems to adapt to their changing environment by synchronizing their timings in response to external stimuli. Previously, we reported clock-controlled adaptive responses to heat-shock and oxidative stress and showed how the circadian clock interacts with BMAL1 and HSF1. Here, we present a similar clock-controlled adaptation to UV damage. In response to UV irradiation, HSF1 and tumor suppressor p53 regulate the expression of the clock genePer2 in a time-dependent manner. UV irradiation first activates the HSF1 pathway, which subsequently activates the p53 pathway. Importantly, BMAL1 regulates both HSF1 and p53 through the BMAL1–HSF1 interaction to synchronize the cellular clock. Based on these findings and transcriptome analysis, we propose that the circadian clock protects cells against the UV stress through sequential and hierarchical interactions between the circadian clock, the heat shock response, and a tumor suppressive mechanism. Genki Kawamura et al. demonstrate that cells are protected against UV stress through cooperative interactions among circadian clock, heat shock response, and a tumor suppression mechanism. This study reports another protective role of circadian clock as an adaptation strategy against cellular stress.